EKSISTENSI MANUSIA DAN KEADILAN SOSIAL KEMANUSIAAN PERPEKTIF TAFSIR RUH AL-MA’ANI AL-ALUSI (IAIN KENDARI, 2023)
The purpose of this research is to identify one step more in Tafsir Ruh Al-Ma'ani by Syihabuddin as-Sayyid Mahmud Afandi Al-Alusi Al-Baghdadi. The strategy in this study is qualitative in nature, including a review of relevant literature and an analysis of the historical context. The difficulties surrounding Al-Ma'ani's Ruh Interpretation, the background of the interpretation and interpreters, the methodology and examples of its placement. Al-Alusi hides the existence of humans on earth only to do good deeds to Allah Swt. What is meant by charity is a matter that includes the charity of the heart and the charity of the limbs. Al-Alusi is the embodiment of justice into three meanings: First, Q.S. Al-An'am verse 152 has justice in matter and immateriality. Material justice is closely related to everything related to creatures. Then, a fair picture is closely related to the theological realm. For those who carry out the principles of justice in accordance with existing regulations, they are entitled to a balanced reward. Second, Q.S. Al-Isra' verse 35 Al-Alusi justice of justice (Al-Qist) uses the word Qabban which means balance or scales. Third, Q.S. Al-Jin verse 14 Al-Alusi expresses it with the meaning of recompense or imbalance due to deviations from religious rules. As incompatible with carrying out religious rules.